Ethyl methacrylate diblock copolymers as polymeric surfactants: Effect of molar mass and composition. (5th July 2021) - Somuncuoğlu, Birsen; Lee, Yu Lin; Constantinou, Anna P.; Poussin, David L.M.; Georgiou, Theoni K.
Graphical abstract: Thermoresponsive polymeric macrosurfactants can be used to stabilise emulsions and then destabilise them using temperature as a trigger. Highlights: Thermoresponsive amphiphilic block copolymers. Amphiphilic diblock copolymers as polymeric surfactants. Composition and molar mass effect on the thermoresponsive and emulsifying properties. Difference between ionic and non-ionic polymeric surfactants. Abstract: Well-defined amphiphilic diblock copolymers and statistical copolymers were synthesised and investigated as polymeric surfactants. Specifically, two series of linear diblock copolymers-totaling 21 copolymers-were studied. In both series, the same hydrophobic monomer (ethyl methacrylate, EtMA) was used, whereas the hydrophilic monomer was changed. The first series was based on the non-ionic hydrophilic monomer, poly(ethylene glycol) methyl ether methacrylate (PEGMA, 300 g/mol), while the second series was based on the ionic, hydrophilic monomer, 2-(dimethylamino)ethyl methyl methacrylate (DMAEMA). The molar mass (MM) and compositions were systematically varied to investigate their effect on the final properties of the polymer. The aqueous solution properties of the copolymers, such as their cloud points, effective p K a values, hydrodynamic diameters, critical micelle concentrations and hydrophile-lipophile balances were determined. The hydrophobic content affected the thermoresponsive ability and the p K a of the polymer solutions significantly. Finally, the emulsifying properties of block copolymers were studied by preparing emulsions containing 1 w/w% of the polymer at the same water to methyl laurate ratio and observing their stability for 1 month. The stability of the emulsions was affected by both the MM and composition of the polymers, but to different extents for the non-ionic compared to the ionic series of polymeric macrosurfactants.